Cardiovascular magnetic resonance of quinticuspid aortic valve with aortic regurgitation and dilated ascending aorta - Zhang Zhaoqi; Zhang Lijun; Meng Yanfeng; Wang Yongmei; Yang Xiaoming (Journal of Cardiovascular Magnetic Resonance, 2009)
Abstract We report a rare case of a quinticuspid aortic valve associated with regurgitation and dilation of the ascending aorta, which was diagnosed and post-surgically followed up by cardiovascular magnetic resonance and dual source computed tomography.